2010
DOI: 10.1007/s11557-010-0663-8
|View full text |Cite
|
Sign up to set email alerts
|

Fungal endophytes associated with the mistletoe Phoradendron perrottettii and its host tree Tapirira guianensis

Abstract: The endophytic mycobiota of leaves and stems of the mistletoe Phoradendron perrottettii and its host tree Tapirira guianensis, two physiologically connected plant species of the Brazilian savannah in southeastern Brazil, were investigated to evaluate host and organ recurrence among endophytes. Leaves and stems of P. perrottettii and leaves of T. guianensis were sampled in the dry and wet season. Stems of T. guianensis were also sampled in the wet season. Endophytes were isolated by an adapted trituration and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 30 publications
1
11
1
1
Order By: Relevance
“…C. globosum was reported to be confined to bark [19] or leaf [38] in earlier studies, but occurred in every tissue in this study. Endophytic fungi often are tissue specific, but most show "only" tissue preference [13,30]. For example, none of the nonxylariaceous species isolated from either leaf or petiole tissue of the palm Trachycarpus fortunei was tissue specific [59] Many workers found that the level of endophytic colonization increased during rainy seasons [48,51,71] and this is in accordance with our results.…”
Section: Discussionsupporting
confidence: 86%
“…C. globosum was reported to be confined to bark [19] or leaf [38] in earlier studies, but occurred in every tissue in this study. Endophytic fungi often are tissue specific, but most show "only" tissue preference [13,30]. For example, none of the nonxylariaceous species isolated from either leaf or petiole tissue of the palm Trachycarpus fortunei was tissue specific [59] Many workers found that the level of endophytic colonization increased during rainy seasons [48,51,71] and this is in accordance with our results.…”
Section: Discussionsupporting
confidence: 86%
“…Some endophytes are known to be tissue specific (de Abreu et al 2010;Fisher et al 1993;Ganley and Newcombe 2006). However, results of this study provided no evidence that the Botryosphaeriaceae sampled are specific to either leaves or woody tissue, although the frequency of occurrence of some species such as S. viticola varied on tissue types.…”
Section: Neofusicoccum Kwambonambiense Represents Another Example Of contrasting
confidence: 64%
“…However, studies on endophytic fungal distribution in parasitic plants and its host are more complicated, for fungal colonization and movement within the two plants can either be facilitated via xylem tubes ( Compant et al, 2010 ) or through apoplasts, intercellular space ( Maheshwari et al, 2013 ). For example, it was found that the mistletoe Phoradendron perrottettii and its host tree Tapirira guianensis shared some common endophyte species while still maintaining distinct communities ( de Abreu et al, 2010 ). Similarly, in our studies ( Figure 2A ) we found that CSR and its host SNT shared much more OTUs (76 in total) for endophytic fungi, compared to CSR and NT (4 in total).…”
Section: Discussionmentioning
confidence: 99%